Assessing the speed, extent, and impact of the diffusion of solar PV. (November 2022) - Morcillo, Jose; Castaneda, Monica; Jímenez, Maritza; Zapata, Sebastián; Dyner, Isaac; Aristizabal, Andres J.
Abstract: Electricity markets are changing towards increases in renewable sources. This technology transformation, as any other, brings opportunities and challenges to the industry. In electricity, the technology transformation is a complex process that impacts different stakeholders in many dimensions. This paper assesses the diffusion of rooftop-solar technology in electricity markets in terms of its extent, speed, and effects, considering prices and services. The analysis includes a comparison of technology transformation in the electricity sector and its effects on stakeholders in the United Kingdom, Colombia, and Brazil. The paper concludes, through a model-based framework, that Photovoltaic diffusion converges in penetrating up to 25%–30% of the residential sector regardless of a country's initial market conditions, industrialization level and solar radiation levels. Additionally, electricity prices for those households that do not use PVs will increase by about 20% by 2040. Finally, the cost recovery of utilities may be affected, though in some cases this may be more severe than in others.